2017
DOI: 10.1089/soro.2017.0028
|View full text |Cite
|
Sign up to set email alerts
|

Stronger at Depth: Jamming Grippers as Deep Sea Sampling Tools

Abstract: Abstract-In this work we experimentally demonstrate (a) that the holding strength of universal jamming grippers increases as a function of the jamming pressure to greater than three atmospheres, and (b) that jamming grippers can be used for deep sea grasping tasks in ambient pressures exceeding one hundred atmospheres, where such high jamming pressures can be readily achieved. Laboratory experiments in a pressurized, water filled test cell are used to measure the holding force of a 'universal' style jamming gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 11 publications
0
39
0
Order By: Relevance
“…The universal jamming gripper has been applied to industrial environment, and several research applications have been demonstrated, such as in prosthetic, assembly tasks, and human‐robot cooperation, as well as integration with learning algorithms . Licht et al employed jamming gripper as an end effector of a remotely operated vehicle for deep sea sampling, and showed that the gripper was able to generate over 35 N of pulling force on a sample (stainless steel rod) at a depth of 1200 m (Figure c). When multiple granule‐filled bags are used as end effectors, granular jamming shows improved versatility to deal with an even larger variety of objects.…”
Section: Gripping By Controlled Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation
“…The universal jamming gripper has been applied to industrial environment, and several research applications have been demonstrated, such as in prosthetic, assembly tasks, and human‐robot cooperation, as well as integration with learning algorithms . Licht et al employed jamming gripper as an end effector of a remotely operated vehicle for deep sea sampling, and showed that the gripper was able to generate over 35 N of pulling force on a sample (stainless steel rod) at a depth of 1200 m (Figure c). When multiple granule‐filled bags are used as end effectors, granular jamming shows improved versatility to deal with an even larger variety of objects.…”
Section: Gripping By Controlled Stiffnessmentioning
confidence: 99%
“…c) Holding force test in deep sea (1200 m depth). Reproduced with permission . Copyright 2017, Mary Ann Liebert.…”
Section: Gripping By Controlled Stiffnessmentioning
confidence: 99%
“…Vacuums have also been employed to create strong contraction with minimal change in actuator radius 28 (Fig. 2a) and enable underwater gripping 29 .…”
Section: Soft Actuationmentioning
confidence: 99%
“…Some efforts have been made to address the limitations, from a compact pneumatic system with chemical reactions (not applicable for underwater application) 30 to jamming grippers with ambient water pressure compensation for object picking with primitive dexterity. 31,32 In particular, an accumulator was made by Phillips et al 33 to both counter ambient pressure and increase the flow rate in the actuation level. A spring was used in the accumulator to hold ambient pressure and provide an increased flow rate.…”
Section: Introductionmentioning
confidence: 99%